Development of highly efficient nickel-doped zeolitic imidazole framework (ZIF-67) based catalyst for methanation reaction - Aldoghachi, Ali Faris Abdulridha (2023)
The conversion of CO2 to synthetic natural gas via methanation reaction is gaining popularity due to its potential to solve long-term energy storage challenges and reduce CO2 emissions. Developing a highly efficient catalyst that can actively function under low reaction temperatures is crucial for the methanation reaction’s sustainability and for making CO2 capture more affordable. Utilizing highly porous metal-organic framework (MOF) materials such as ZIF-67 as catalyst support with added Ni would be an interesting endeavor to achieve good dispersion and resist agglomeration of dopants during methanation reaction. Therefore, ZIF-67 was prepared using 2-methylimidazole and cobalt nitrates, and the obtained ZIF-67 solid was activated under a vacuum oven overnight at 80 °C. Nickel dopant was incorporated onto ZIF-67 in the range of 1-12 wt% via wet-impregnation method, and the catalyst precursor was calcined at 350 °C for 4h under N2 flow. The prepared catalysts were characterized using Brunauer-Emmett- Teller (BET), X-ray diffraction (XRD), Thermogravimetric analysis (TGA), Fouriertransform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Temperature-programmed desorption of carbon dioxide (TPD-CO2), Temperatureprogrammed reduction (TPR), and High-resolution transmission electron microscopy (HRTEM). Prior to the methanation reaction, 0.05g of catalyst was loaded into a fixed tubular reactor and reduced in situ under (5% H2/balanced Ar) flow at 350 °C for 3h. Subsequently, the flow is switched to reactant gas for catalytic testing at a predetermined reaction temperature. Preliminary catalytic methanation reaction was carried out at a temperature of 400°C, with a flow rate of 108,000 mL.g-1.h-1 and feedstock gas (H2/CO2) ratio of 4:1. The physicochemical characterization of the prepared catalysts exhibit very high surface area and porosity along with evenly distributed Ni dopants over ZIF-67 support. The catalysts were found to be active in CO2 conversion, whereby the presence of Ni significantly influences the product selectivity of the reaction. Based on the catalytic screening results, 8wt% Ni/ZIF- 67 catalyst was deemed the most active among the other prepared catalysts in the methanation reaction, with a moderate CO2 conversion of 56% followed by selectivity of 96% at a reaction temperature of 300°C.